(untitled) (ART AND CULTURE BULLETIN, 2024)
In this article, the emergence and development of writing, the development of society, as well as the need for people to communicate at a distance from each other, to record information of a political, legal, religious and aesthetic nature, as well as how the peoples of Central Asia used different types of writing.